Studying the effect of colored LED lights on reducing production costs in broiler poultry sheds compared to traditional lights - محمد جعفر; علي نيصافي; محمد سلهب; بشرى العيسى (Latakia University Journal -Biological Sciences Series, 2023)
The research was carried out in one of the private poultry farms in Lattakia Governorate from 28/4/2022 to 11/6/2022, with an area of ​​80 m2. The care was carried out in a semi-closed model barn. The barn was divided into five sections (transactions) by means of insulating barriers, and each section included Three replicates, and 300 unsexed (ROSS) broiler chicks were used in the experiment at a rate of (10) birds/m2, all day-old chicks were weighed, and chicks were randomly distributed within five different treatments according to the color and type of lamps light (LED Green G, LED Blue B, LED is a mixture of blue and green, Mix B+G, fluorescent white W, tungsten yellow Y), and all housing, care and feeding conditions were the same for all treatments. The results of the experiment showed that the replacement of traditional lamps with colored LED lamps reduced the electrical energy consumption needed to light the sheds by (91)% and reduced the mortality rate, which amounted to 0%, 1.7%, 1.7% in the LED lamps treatments. (TMix B+G , T B , TG) respectively, while it reached 6.7%, 5% in the treatments of conventional lamps (Tungsten TY, fluorescent Tw) respectively. Birds exposed to TMix B+G LED lamps also outperformed the rest of the other treatments in weight gain, as the average Weight (2825.4) g compared to an average weight of (2610) g for birds exposed to tungsten lamps, and with a high conversion efficiency (average conversion factor 1.70 for birds treated with LED TMix B+G versus 1.79 for birds exposed to tungsten lamps), LED to reduce production costs.